2021
DOI: 10.2147/ijgm.s342286
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CIRBP and TRPV4 as Immune-Related Diagnostic Biomarkers in Osteoarthritis

Abstract: Osteoarthritis (OA) is the most common chronic joint disorder in elderly individuals. This study aimed to identify immune-related diagnostic gene signatures for OA. Methods: First, we performed single-sample gene set enrichment analysis (ssGSEA) to evaluate the infiltration of immune cells in OA expression data from the Gene Expression Omnibus (GEO) database. Then, weighted gene coexpression network analysis (WGCNA) was performed to identify hub modules and genes related to immune cell types with significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…As a whole, these hub genes are valuable for being recognized as diagnostic biomarkers of OA. It has also been observed that several studies reported some diagnostic biomarkers in osteoarthritis, which were different from the hub genes found or derived from the same gene family [ 38 - 40 ]. The possible reasons might be the differences in the resources of the datasets analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…As a whole, these hub genes are valuable for being recognized as diagnostic biomarkers of OA. It has also been observed that several studies reported some diagnostic biomarkers in osteoarthritis, which were different from the hub genes found or derived from the same gene family [ 38 - 40 ]. The possible reasons might be the differences in the resources of the datasets analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is the most common arthritis leading to ache, joint destruction, and eventually handicap; women and the aged are disproportionately affected by this disease (1)(2)(3). The combined effects of an aging global population, the increasing incidence of obesity and numbers of joint trauma have led to this disease becoming much more prevalent, with a minimum of 500 million people estimated to be affected by OA worldwide (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Least absolute shrinkage and selection operator (LASSO) regression analysis can shrink the regression coefficients of some variables to zero by imposing constraints on the model parameters, so it retains the advantages of subset shrinkage and minimizes the prediction error [ 23 ]. It has been successfully applied in bioinformatics analysis and clinical research related to KOA [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%